2004
DOI: 10.1111/j.1600-0528.2004.00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective use of fluorides for the prevention of dental caries in the 21st century: the WHO approach

Abstract: Despite great improvements in the oral health of populations across the world, problems still persist particularly among poor and disadvantaged groups in both developed and developing countries. According to the World Oral Health Report 2003, dental caries remains a major public health problem in most industrialized countries, affecting 60-90% of schoolchildren and the vast majority of adults. Although it appears that dental caries is less common and less severe in developing countries of Africa, it is anticip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
266
1
41

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(325 citation statements)
references
References 4 publications
4
266
1
41
Order By: Relevance
“…According to the WHO Report, dental caries affects 60-90 % of schoolchildren and the vast majority of adults, indicating how massive the extent of this public health problem actually is so that it emerges in the majority of industrialized countries (25). Children population from 5 to 6 year-old are of interest in relation to caries levels in the primary dentition, which may exhibit changes over a shorter timespan than in the permanent dentition at ages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the WHO Report, dental caries affects 60-90 % of schoolchildren and the vast majority of adults, indicating how massive the extent of this public health problem actually is so that it emerges in the majority of industrialized countries (25). Children population from 5 to 6 year-old are of interest in relation to caries levels in the primary dentition, which may exhibit changes over a shorter timespan than in the permanent dentition at ages.…”
Section: Discussionmentioning
confidence: 99%
“…Prema podatcima SZO-a, od 60 do 90 posto školske djece i velika većina odraslih imala je karijes, što upućuje na njegovu rasprostranjenost i javnozdravstveni problem koji se pojavljuje u većini industrijaliziranih zemalja (25). Djeca u dobi od 5 do 6 godina interesna su skupina zbog karijesa koji se pojavjuje u mliječnoj denticiji i promjena koje nastaju u kraćem razdoblju u odnosu na trajnu denticiju kod djece starije dobi.…”
Section: Raspravaunclassified
“…Another important factor in the prevention of oral diseases is fluoridation of the public water supply, considered one of the ten most relevant public health measures in the 20 th century 33 . This measure has been the focus of numerous studies, and has been recommended by the WHO as an important factor for offsetting oral health inequalities in public health 34 . Water supply fluoridation is capable of reducing prevalence and incidence of dental caries in various age groups, decreasing treatment costs for oral diseases and reducing the inequalities between Note: values in boldface are statistically signifi cant (p < 0.01); variables adjusted for others at the same level and higher.…”
Section: Discussionmentioning
confidence: 99%
“…2,41 The World Health Organization has reported that fluoridation has substantial advantages, especially for high-risk groups, when it is culturally acceptable and technically feasible. 42 A recent unpublished study performed in Alaskan communities revealed a reduction in caries of 30% to 50% with community fluoridation, even when other risk factors were accounted for (Michael Bruce, Arctic Investigations Program, Centers for Disease Control and Prevention, verbal communication, June 6, 2009). In North America, there is wide disparity in the access to water fluoridation.…”
Section: Fluoridementioning
confidence: 99%